Rancang Bangun Sistem Informasi Arsip Digital Berbasis Web (Studi kasus: PT. Sentral Kreasi Inovasi) - Robi Sobian; Surtikanti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Technological developments are flowing fast, especially information technology, which will have a big impact on human life. The need for human beings for information technology is really needed so that they can receive fast and accurate information services. Related to searching for archives and storing archives, I'm currently using the manual system. If you want to collect information about archives, you need old times, especially with the condition that the number of archive volumes is being passed from year to year. The Data Management System is now a very necessary choice for government and private agencies. Because it can make efficient use of storage boards, easy to use data collection, easy to search and monitor archives and neatly archiving letters or documents from ana ing institutions. According to Ing Ndhuwur's description, it's also important that the documents that are very important for the company must be kept neatly and easy to find. Storage of mesthine physical archives must be taken care of as well as stored archives will add to the challenge and the multitude of demands for speed and accuracy of remote kanthi archive services. Then an application will be designed "Design and Build a Web-Based Digital Archive Information System at PT. It is hoped that this digital archive information system can help collect documents quickly and efficiently when needed, the System Development Method Application Design and the process of compiling this thesis, the author uses the Waterfall method, data collection can be carried out using various settings, various -various sources, and various methods. If a company can add and use a data management system and use a conventional system into a structured and computerized system, the Kanthi Kasedhiya Web-Based Digital Archive Application System can collect archival data easily and with a structured name when uploading.